Convergence between the Marketing System & AI (The beginnings of the IR 5.0 & the birth of Algorithmic Marketing Age) - Guendouz, Tarek Ahmed (Journal of Economic, Administrative and Legal Sciences, 2024)
This study aims to shed light on an interesting topic: the long-term partnership between marketing approaches and computer-enabled AI tools. This strategic alliance comes in light of the emergence of a fifth industrial revolution based on cyber-physical systems (CPS), which had considered a massive global event. In this context, the research paper concluded that automating the marketing decision through collaborative robots and machine learning solutions leads to gaining a sustainable competitive advantage enhanced by digital and technical innovation, it appears in the hyper-customization (personalization) of customers experiences (CX), which results in an increase in sales and profits under the umbrella of algorithmic marketing.